Problems and prospects in teaching multidisciplinary courses: a case study of human resource information systems. (2nd October 2007) - Thite, Mohan; Kerr, Don; Sandhu, Kuldeep
This paper identifies and explores the issues, challenges and strategies in the design, development and administration of a suitable Human Resource Information System (HRIS) curriculum. Many academics have limited experience in teaching cross-disciplinary subjects and are further constrained by the cost and technical difficulties in deploying relevant software packages for hands-on experience by students. Another challenge is the variation in students' abilities when undertaking such a course with classes typically having a mix of information systems and human resource students. The paper uses a case study approach to analyse key issues and explore possible strategies for improvement.